Wheat Cost-Return Budget in Northeast Kansas - Dhuyvetter, Kevin C. (My University, 1998)
This publication projects a budget that reflects expected income and costs based on wheat production in northeastern Kansas.
MF572_1998_10
Keywords: MF572; Economics; Crops; MF